2011
DOI: 10.1002/j.2055-2335.2011.tb00677.x
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of a Quality Clinical Placement in Pharmacy: Stakeholder Perspectives

Abstract: Background The educative role of experiential workplace placements has been discussed in the context of many health professions. Quality assurance and enhancement strategies rely on evaluations that provide valid and reliable data, so that informed decisions can be made about improving learning for students. No research could be located in the literature to determine the gap between stakeholders' perceptions of the importance of indicators and their perceptions of whether these practices occur in experiential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This may be a finding which is peculiar to Australian pharmacy practice or a finding which is peculiar to work as opposed to placements as part of a degree program. Studies in Australia have indicated that the linking of theoretical knowledge to activity in clinical pharmacy placements is viewed by students, academics and clinical placement preceptors as contributing to quality clinical placements 19. Additionally, there is evidence for this linkage in Australian clinical pharmacy placements 19.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be a finding which is peculiar to Australian pharmacy practice or a finding which is peculiar to work as opposed to placements as part of a degree program. Studies in Australia have indicated that the linking of theoretical knowledge to activity in clinical pharmacy placements is viewed by students, academics and clinical placement preceptors as contributing to quality clinical placements 19. Additionally, there is evidence for this linkage in Australian clinical pharmacy placements 19.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Australia have indicated that the linking of theoretical knowledge to activity in clinical pharmacy placements is viewed by students, academics and clinical placement preceptors as contributing to quality clinical placements 19. Additionally, there is evidence for this linkage in Australian clinical pharmacy placements 19. Similarly, specifically in Finland, studies have indicated that many students felt they were able to link their theoretical knowledge to their activity in clinical pharmacy placements 20.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation